Políticas públicas no combate à desigualdade racial : uma análise da implementação da Lei nº 12.990/2014 em uma Instituição Federal de Ensino Superior - Rodrigues, Lilian Segnini (Universidade Federal de São Carlos, 2017)
The issue of public policies for affirmative action, especially the reservation of vacants for blacks, whether on admission to the University or on the public service, is quite controversial. There are many arguments against this type of policy, notably involving meritocracy. However, the high level of racial inequality in Brazil makes these public policies necessary, since universalist policies of inclusion have proved insufficient over time to guarantee equal opportunity for blacks. In this sense, after the reservation of vacancies for blacks in universities, it is time for the state to intervene in the labor market. The Law 12,990 / 2014, which reserves for blacks 20% of the vacancies of public tenders for a period of ten years, within the Union, is hereby enacted. The objective of this research, therefore, is to analyze the implementation of this public policy in a Federal Institution of Higher Education (IFES), located in the State of São Paulo, identifying the fragilities and proposing improvements in this stage of the process. For that, a bibliographic survey is done, besides a case study, whose empirical object is the Federal University of São Carlos. To contribute to the proposals for improvement in the implementation of this public policy, interviews were made with members of two different black movements. It is concluded that the process of implementing this law can be improved in order to increase the number of vacants reserved for blacks. In addition, is raise the debate about the verification process of the veracity of self-declaration, involving the difficulty of establishing objective criteria. The proposed improvements involve, in particular, the awareness of the implementing agents.
Public policies in combating racial inequality : an analysis of the implementation of Law nº 12,990 / 2014 in a Federal Institution of Higher Education
Keywords: Ações afirmativas; Implementação de políticas públicas; Instituições Federais de Ensino Superior; Lei 12.990/2014; Affirmative actions; Implementation of public policies; Federal Institutions of Higher Education; Law 12.990/2014; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::ORGANIZACOES PUBLICAS